A Review on Sources, Hydrochemical and Temporal Changes of Arsenic Contamination in the Groundwater of Ballia and Ghazipur Districts, India - Akbare Azam; Hemant Kumar Nirala; J. K. Pandey; Ruby Ahmed; Trinath Mishra; Manisha; Sankatha Prasad Sonkar; Awanish Kumar Pandey (Geography, Earth Science and Environment: Research Highlights Vol. 7, 2025)
Arsenic contamination in groundwater has emerged as a significant environmental and public health challenge, both nationally and globally. Recent assessments of groundwater samples from key regions in the north-eastern states of India reveal arsenic concentrations ranging from 50 to 986 µg/L, exceeding the permissible limits set by the World Health Organization (WHO) and the Bureau of Indian Standards (BIS), which are 10 µg/L and 50 µg/L, respectively. The seasonal behavior of arsenic is largely governed by geochemical processes, wherein iron (III) oxyhydroxide decomposition during the monsoon season releases arsenic into the groundwater, while its adsorption onto iron (III) oxyhydroxide occurs during the pre-monsoon season. This study examines the sources, hydro-chemical characteristics, and seasonal variations of arsenic in groundwater within the Ballia and Ghazipur districts of Eastern Uttar Pradesh. As predicaments in the environment are due to its mobilization under natural geogenic conditions as well as anthropogenic activities. Arsenic mineral is not present in As contaminated alluvial aquifer but As occurs adsorbed on hydrated ferric oxide (HFO) and generally coats clastic grains derived from Himalayan mountains. As is released to the groundwater mainly by bio-remediated reductive dissolution of HFO with corresponding oxidation of organic matter. The development of strongly reductive dissolution of mineral oxides (Fe and Mn) at near-neutral pH may lead to desorption and ultimately release of As into the groundwater. As release through the geochemical process is a more important factor in alluvial aquifers causing As contamination rather than sources of arsenic. During the monsoon, rising water tables and flood conditions contribute to arsenic dilution, whereas prolonged moisture retention restricts groundwater movement, affecting arsenic dispersion. This study highlights the impact of hydrological cycles on arsenic behavior, providing insights for effective groundwater management in arsenic-affected regions.